An eco-friendly process for biobleaching of eucalyptus kraft pulp with xylanase producing Bacillus halodurans. (15th January 2015) - Sharma, Prince; Sood, Chandni; Singh, Gursharan; Capalash, Neena
Abstract: Xylanase-producing Bacillus halodurans FNP 135 was applied for biobleaching of kraft pulp through submerged (SmF) and solid state fermentation (SSF). SmF showed better delignification than SSF with 35 and 30% decrease in kappa number, 5.8 and 4.3% increase in brightness, 8.7 and 6.7% increase in breaking length, 13.7 and 12% increase in burst factor, 20.7 and 17.5% increase in tear factor and 8.6 and 3.3% increase in viscosity respectively. Surface composition of SmF treated pulp fibers and morphological characteristics were studied by X-ray diffraction, Fourier transform infra red spectroscopy and scanning electron microscopy. Significant changes were observed in fiber surface functional groups indicated delignification and cellulose crystallinity increased marginally. Biobleaching resulted in 20 (SmF) and 10 (SSF) % reduction in chlorine consumption. Electron microscopy revealed that fiber surface became more fibrillar and rough with an appearance of pores and flakes on it. The present work can help to make the paper manufacturing process cleaner and ecofriendly. Highlights: Biobleaching of hardwood eucalyptus kraft pulp directly with Bacillus halodurans culture. No need to produce the xylanase enzyme for biobleaching thus saving hugely on cost and time. Significant reduction in the use of hazardous and toxic chlorine based chemicals for whitening of paper.